Study protocol for the description and evaluation of the "Habit Coach" - a longitudinal multicenter mHealth intervention for healthy habit formation in health care professionals - Anna Vogelsang; Clara Hinrichs; Lena Fleig; Ines Pfeffer (BMC, 2022)
Abstract Background The adoption of a healthy lifestyle plays a crucial role for the health and well-being of health care professionals. Previous e- and mHealth interventions relied on deliberative psychological processes (e.g., intention, planning) to target lifestyle changes, while revealing mixed efficacy. The additional potential of non-deliberative, automatic processes (i.e., habits) for behavior change has been understudied in interventions so far. The Habit Coach mHealth intervention combines deliberative and non-deliberative processes to support health care professionals in forming healthy physical activity, nutrition and mindfulness habits in daily life. The aim of this paper is to outline the study protocol including a detailed description of the mHealth intervention, evaluation plan, and study design. The purpose of this trial is to understand healthy habit formation in health care professionals over time. Methods A one-arm, multicenter mHealth intervention study will be conducted. Behavioral and psychosocial predictors will be collected via within-app questionnaires across a 100-day period at baseline, post, as well as at weekly assessments. To understand habit formation across time, linear mixed models will be used. Discussion This trial aims to unravel the role of motivational and volitional determinants for healthy habit formation across multiple health behaviors in health care professionals embedded in a mHealth intervention. Trial registration This trial is registered in the German Clinical Trials Register, DRKS-ID DRKS00027156. Date of registration 17 November 2021.